Transfusion‐transmitted malaria not preventable by current blood donor screening guidelines: a case report. Issue 9 (13th June 2016) - Holtzclaw, Arthur; Mrsic, Zorana; Managbanag, Jim; Calvano, Tatjana; Colombo, Christopher
Abstract : BACKGROUND: Transfusion‐transmitted malaria (TTM) is a well‐known, though rare, entity in the United States with only 100 cases previously reported. With no Food and Drug Administration–approved screening tests of donated blood for malaria in the United States, prevention relies solely on deferral of the highest‐risk donors. We present a case of TTM not preventable by these guidelines. CASE REPORT: A 76‐year‐old male presented with fever, hypotension, tachycardia, and a urinalysis consistent with a urinary tract infection. He was admitted to the intensive care unit and initiated on broad‐spectrum antibiotics. On Hospital Day 2, he was incidentally found to have intraerythrocytic parasites on a peripheral smear, identified as Plasmodium malariae by polymerase chain reaction and was treated successfully with atovaquone‐proguanil. The patient had no recent foreign travel or exposure to malaria but had received 15 units of blood products in the past 6 years. Index samples from the 10 most recent units were obtained, with one testing positive for P. malariae via serology. The donor was a 20‐year‐old male who immigrated to the United States from Liberia at the age of 5 with no subsequent travel or exposure to malaria. DISCUSSION: A review of current literature demonstrated that 71% of TTM cases occur from imperfect application of the current deferral guidelines. In this case, however, 15 years had elapsed between the donor's immigration and the transmission of the disease, placing him well outside any current deferral period. As such, the case demonstrates the need for continued development of highly sensitive and cost‐effective laboratory screening for high‐risk donors.